Molecular and physico-chemical characterization of de-structured waxy potato starch. (August 2021) - Ang, Cai Ling; Matia-Merino, Lara; Lim, Kaiyang; Goh, Kelvin Kim Tha
Abstract: This study focuses on the physico-chemical properties of a "clean-label" modified starch (de-structured starch) as a potential food ingredient. The modified starch was obtained by the disassembly of native waxy potato starch granules into its macromolecular chains. Waxy potato starch samples were treated at elevated temperatures of 120, 130, 140, and 150 °C for 30 min at a stirring speed of 300 rpm in a high pressure reactor. Starch treated at 120 °C showed similar molar mass as its native form indicating that treatment at 120 °C had resulted in the disassembly of the starch granules into its macromolecular chains. Reduction in viscosity and particle size was observed with increased temperature from 120 to 150 °C. The reduction in viscosity and size was not only attributed to the disassembly of starch granules into its macromolecular fractions but also due to a further size reduction of amylopectin chains. De-structured starch treated at 140 and 150 °C exhibited flow behavior approaching Newtonian fluid. However, de-structured starch treated at 120 and 130 °C exhibited shear-thickening behavior above their critical shear rates at 14 and 27 s −1 respectively. Shear-induced interactions among starch macromolecular fractions appeared to have occurred within a narrow range of heat treatment (120 and 130 °C) but not in more severely heat-treated starches (140 and 150 °C). Graphical abstract: Image 1 Highlights: De-structured starch was obtained using a high pressure stirred reactor at ≥ 120 °C for 30 min. De-structured starch viscosity decreased with increased treatment temperature of 120–150 °C. Molar mass of de-structured starch (120–150 °C) ranged from 3.6 × 10 8 to 4.1 × 10 7 Da. De-structured starch treated at 120 and 130 °C exhibited shear-thickening properties.